Ottoman supremacy and the political independence of the Balkan and Central European states - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2023)
The article deals with the nature of the political relationship between the Ottoman Empire and the Balkan states. The various forms of dependency led to varied limitations on the functioning of these states, especially in the field of their international politics. The Ottoman Empire's relations with weaker, allied, vassal and subordinate states were shaped by the following factors: the historical period, the political and legal nature of the mutual relations, religion, the current political and military situation. On the basis of analysis of the sources and scientific literature, it has been shown that the Ottoman Empire was unable to prevent more or less official policy by its subordinate centres, as long as they had any state structures (even if they were only of a self-governing nature). In the 14th century, most of the Balkan states found themselves as allies and tributaries of the Ottoman Empire. The alliance with the Ottomans did not limit political relations with countries uncommitted against the Ottomans. In the 15th century there was a process of more and more clearly political subordination of the Balkan states which added two important elements to earlier financial and military obligations - investment and obedience. In the 16th century, it was extremely important to surrender to the King of Hungary John Zápolya under the authority of Sultan Suleiman. It also resulted in the Ottoman Empire taking over direct political control of the Romanian principalities: Wallachia and Moldavia. The Sultan was not able to fully control them, they often carried out independent political activities, connected with the Poland-Lithuanian Commonwealth, the Holy Empire, and Transylvania. In the 18th century the process of building the Balkan nation states launched, albeit very slowly. In the 19th century, any independence, even very limited, was conducive to the rapid formation of their own independent statehood.